Over a million students use our free study notes to help them with their homework
First we substitute one x or y into the other equation. The easiest one to put in in this case would be the y in equation (2). So putting the y into (1) you get x^2 + (2x-3)^2=41. Then we expand out the b...
(1+2x^2)/(3x-2)(x-1)^2 = -5/x-1 + 3/(x-1)^2 + 17/3x-2
We know that (x+2) divides p(x), therefore p(x) can be written as p(x) = (x+2)q(x) + 0, where q is another polynomial of degree 2. We can calculate then p(-2): p(-2)= ((-2)+2)q(-2) = 0;p(-2)= (-2)...
When presented with a simultaneous equation, you need to find out the values of the letters (commonly x and y). You might be given two equations such as: a) 2x + 4y = 6, and b) -4x - 3y = 3. The first thi...
Complete the square:x2+4x gives (x+2)2-4y2+2y gives (y+1)2 -1Therefore,(x+2)2-4+(y+1)2 -1=20Rearranging gives:(x+2)2+(y+1)...
←
752
753
754
755
756
→
Internet Safety
Payment Security
Cyber
Essentials